2008
DOI: 10.1016/j.heares.2008.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Distortion-product otoacoustic emissions in the common marmoset (Callithrix jacchus): Parameter optimization

Abstract: Distortion-product otoacoustic emissions (DPOAEs) were measured in a New World primate, the common marmoset (Callithrix jacchus). We determined the optimal primary-tone frequency ratio (f(2)/f(1)) to generate DPOAEs of maximal amplitude between 3 and 24 kHz. The optimal f(2)/f(1), determined by varying f(2)/f(1) from 1.02 to 1.40 using equilevel primary tones, decreased with increasing f(2) frequency between 3 and 17 kHz, and increased at 24 kHz. The optimal f(2)/f(1) ratio increased with increasing primary-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 73 publications
2
24
2
Order By: Relevance
“…To determine the slopes of individual I/O functions, we fitted a linear-regression equation to the linear portion of the functions (Valero, Pasanen et al 2008) and termed it low-level slope. In most animals, the linear growth occurred between L1= 50 to 60 or 65 dB SPL, and the functions tended to saturate at 70–75 dB SPL.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine the slopes of individual I/O functions, we fitted a linear-regression equation to the linear portion of the functions (Valero, Pasanen et al 2008) and termed it low-level slope. In most animals, the linear growth occurred between L1= 50 to 60 or 65 dB SPL, and the functions tended to saturate at 70–75 dB SPL.…”
Section: Resultsmentioning
confidence: 99%
“…These correspond to stimulus-frequency ratios (f2/f1 ratios) of 1.01–1.45. The f2/f1 range was chosen because it encompasses the commonly used ratio, which is 1.22, in most DPOAE studies (Harris, Lonsbury-Martin et al 1989, Lasky, Snodgrass et al 1995, Valero, Pasanen et al 2008). The stimulus level of f1, L1, was fixed at both 75 dB SPL and 20 dB above animals’ hearing threshold at 8 kHz.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anatomical evidence supporting the similarity of the marmoset cochlea to that of humans comes from the work of Spatz and Lohle (1995), which indicated that the marmoset cochlea has 2½ turns, as in humans. Physiological data supporting this similarity come from a recent study on the measurement of otoacoustic emissions (sounds emitted by the ear in response to stimulation): using a noninvasive technique that measures outer hair cell function Valero and colleagues (2008) showed that the acoustical stimulation parameters required to elicit the strongest emissions are similar to those of humans and Old World primates. Taken together, these studies suggest that cochlear parameters may be largely conserved in humans and nonhuman primates.…”
Section: Established and Developing Uses Of Marmosets In Research On mentioning
confidence: 90%